Socio-Economic Factors Affecting Rice Farmers' Decisions Using Direct Seed Planting Technology (Tabela) and Without Tools in Ujung Tanah Village, Mare Sub-District, Bone District, South Sulawesi - Aksari, Riski Ika; Taridala, Sitti Aida Adha; Mappasomba, Musadar (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2021)
This study analyzes socio-economic factors based on age, education, farming experience, labor, and land area on lowland rice farmers' decision-making using Tabela (direct seed planting) with and without tools in Ujung Tanah Village, Mare Sub-District of Bone District. South Sulawesi. This research was conducted in January-December 2020. This research was conducted in Ujung Tanah Village, Mare Sub-District, Bone District. The population in this study were all lowland rice farmers in Ujung Tanah Village, as many as 347 farmers. Determination of the number of samples was carried out in 2 ways, namely the census method for Tabela tool farmers by taking the total population of 15 farmers and for Tabela farmers without tools by taking 10% members of 10 farmer groups with 332 population numbers, determining the sample using the cluster proportional random sampling technique. With 33 farmers, the total of the samples in this study were 48 people. The data method is logistic regression analysis. The results of this study are that the socio-economic factors that influence the decisions of lowland rice farmers in the use of direct seed planting technology (Table Toola), namely the farming experience variable and the land area variable have a negative effect. In contrast, the labor variable has a positive impact.